Perioperative Corneal Abrasion: An Exploration of Certified Registered Nurse Anesthetists’ Preferences for Corneal Abrasion Prevention - Chukala, Christopher (My University, 2022)
Corneal abrasions are the most common ophthalmic complication that occur during general anesthesia, resulting in 2-3% of anesthesia malpractice suits. However, no studies were found in current literature that addressed assessment of anesthesia providers’ knowledge, preferences, and practices for prevention of corneal abrasions. This quality improvement (QI) project assessed seven Certified Registered Nurse Anesthetists’ (CRNA) knowledge of, preferences for, and practice of corneal abrasion prevention, as well as their perceptions of the adequacy of a quick access reference guide as a useful tool for their practice. The CRNAs were asked to complete a pre-implementation survey, utilize an electronic and paper copy of a newly created quick access reference guide over a two-week period, and then complete a post-implementation survey. Analysis of the data reflected a positive improvement in CRNAs’ confidence regarding corneal abrasion diagnosis, prevention, and treatment. Limitations of this study include a short time frame and small sample size. A larger sample size and extended duration of time for the study to take place would strengthen results and help identify best practice methods for corneal abrasion prevention.
Keywords: corneal abrasion, prevention, quick access reference guide, certified registered nurse anesthetist